Co-breeding association of Aedes albopictus (Skuse) and Aedes aegypti (Linnaeus) (Diptera: Culicidae) in relation to location and container size - Nur Aida Hashim; Abu Hassan Ahmad; Anita Talib; Farida Athaillah; Kumara Thevan Krishnan (Nur Aida Hashim, Abu Hassan Ahmad, Anita Talib, Farida Athaillah and Kumara Thevan Krishnan (2018), 2018)
The occurrence of major outbreaks of dengue, and other vector borne diseases such as chikungunya and zikain tropical and subtropicalregions has rendered control of the diseases a top-priority formany affected countries including Malaysia. Control of the mosquito vectors Aedes aegypti and Aedes albopictus through the reduction of breeding sites and the application of insecticidesto kill immature forms and adults are the main control efforts to combat these diseases. The present study describes the association between Ae. albopictus and Ae. aegypti in shared breeding sites. This study is important given that any measure taken against one species may affect the other. A yearlong larval survey was conducted in four dengue endemic areas of Penang Island.Sorenson’s coefficient index indicated that no association between number of the immatures of the two species regardless of container size and study location.Therefore, the mean number Ae. albopictusimmature was not decreased in the presence of Ae. aegypti in shared breeding container. However Ae. aegypti appeared to prefer breeding in habitats not occupied by Ae. albopictus, the two species sharing breeding sites only where available containers were limited. In control efforts, eliminating the preferred breeding containers for one species might not affect or reduce the population of the other species.